2021
DOI: 10.1182/blood.2020009404
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate induces ferroptosis and impairs NF-κB/STAT3 signaling in DLBCL

Abstract: Despite the development of novel targeted drugs, the molecular heterogeneity of diffuse large B-cell lymphoma (DLBCL) still poses a major therapeutic challenge. DLBCL can be classified into at least two major subtypes, i.e. germinal center B-cell-like (GCB) and the aggressive activated B-cell-like (ABC) DLBCL, each characterized by specific gene expression profiles and mutation patterns. Here we demonstrate a broad anti-tumor effect of dimethyl fumarate (DMF) on both DLBCL subtypes, which is mediated by the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 63 publications
2
60
1
Order By: Relevance
“…Inhibition of NFS1 can induce ferroptosis and slow tumor growth in lung adenocarcinoma ( Alvarez et al, 2017 ). STAT3 is the target of ferroptosis in cancer cells, and impaired STAT3 signaling induces ferroptosis in diffuse large B-cell lymphoma cells ( Chen et al, 2021 ; Schmitt et al, 2021 ). Each patient’s risk score was calculated according to the formula.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of NFS1 can induce ferroptosis and slow tumor growth in lung adenocarcinoma ( Alvarez et al, 2017 ). STAT3 is the target of ferroptosis in cancer cells, and impaired STAT3 signaling induces ferroptosis in diffuse large B-cell lymphoma cells ( Chen et al, 2021 ; Schmitt et al, 2021 ). Each patient’s risk score was calculated according to the formula.…”
Section: Discussionmentioning
confidence: 99%
“…DLBCL can be divided into two main subtypes of germinal center B cell-like (GCB) and aggressive activated B cell-like (ABC), both of which has their own specific gene expression profile and mutation pattern. Schmitt et al ( 129 ) investigated the antitumor mechanism of dimethyl fumarate (DMF) against DLBCL. Corresponding results revealed that DMF had a broad antitumor effect on both DLBCL subtypes, which is mediated by the induction of ferroptosis.…”
Section: Application Of Ferroptosis In Hematologic Malignanciesmentioning
confidence: 99%
“…As an iron-catalyzed form of regulated necrosis, ferroptosis is involved in the silencing or downregulation of genes initiating or executing necroptosis in cancers [ 38 , 39 ]. DLBCL outcome is the result of interactions between the genetic abnormalities of ferroptosis-related factors and the clinical status of the patients [ 31 , 40 ]. Identification of clinical risk is helpful to better design the therapeutic intervention in different DLBCL patients [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%